Avaliação do condicionamento dentinário com ácidos naturais biomodificadores na interface dentina-resina - Macedo, Francisco Adeilson Alves de (2018)
In the attempt to reduce the failures in restorative procedures, alternatives have been proposed, such as the use of dentin biomodifying agents, in order to promote improvements in the physical and mechanical properties and to protect the collagen fibrils from the degradation. The present study aims to evaluate the use of phytic acid (IP6), tannic acid (TA) and gluteraldehyde as biomedical agents during dentin conditioning, both in wet and dry techniques, and as conditioning affected the bond strength, sealing and nanoleakage in interface. Seventy-two teeth were prepared exposing the dentin surface to perform the tests microtensile bonding strength (n=6), nanoleakage evaluation (n=1) and the micropermeability(n=2). Therefore divided into 8 groups according to the etched acid and technique used in restorative procedures. The dentin surfaces were conditioned with 37% phosphoric acid (control), 37% phosphoric acid + 5% glutaraldehyde, 1% phytic acid (IP6) (pH 1.2) and 20% tannic acid (TA) (pH 2.8), then rinsed and air dried. In the wet technique, after drying, dentin was rehydrated for 60s. The adhesive Adper Single Bond 2 was applied and restored in increments of 1mm up to the height of 5mm. The restored teeth were sectioned to obtain toothpicks with a cross-sectional area of 1.0 mm2. Half of the specimens were immediately tested, while the others were after six months, with the exception of the micropermeability test, which were only tested immediately.In statistical analysis, the Anova and Tukey tests were used. After 24 h and 6 months, respectively, the only means of bond strengths of the tannic acid group were significantly lower than those found in the other groups in both techniques (p <0.05). In the nanoleakage evaluation, in the dry technique, the IP6 group presented better sealing and less infiltration, and the TA group presented higher concentration of nitrate at the interface. In the wet dentin, the IP6 group presented higher infiltration and lower sealing, and the TA group preserved the interface after 6 months. In the micropermeability, in the dry and wet techniques, the groups IP6 and TA showed a better sealing and less infiltration of fluorescein. The etched with IP6 and TA, in dry and wet technique respectively, preserved the adhesive interface, after 6 months, as well as the control group.